Folk-Tales of Kashmir - Knowles, J. Hinton, (Brill | Manohar Publishers & Distributors, 2024)
Kashmir has a long history stretching back to prehistory, where many caves and other archaeological findings were discovered. The region's name is found in Mahabharata and other Puranic texts, including the most famous Rajatarangini by Kalhana. Also, Sanskrit commentaries written by popular commentators Abhinavagupta, Vasudeva, Utpala, and others contributed immensely to the history of Kashmiri literature in the early medieval period. During the advent of Islamic rule, many Kashmiri writers, such as Lal Ded, Habba Khatoon, Nund Rishi, Rupa Bhavani, etc., wrote Sufi, mystical, romantic, and devotional prose, which became the source of rich Kashmiri literary tradition. This book is a collection of 64 different Kashmiri folk tales from different parts of Kashmir, which were composed during the pre-modern period.